FAKTOR-FAKTOR YANG MEMENGARUHI PEMBIAYAAN BERBASIS BAGI HASIL (EQUITY FINANCING) PADA BANK SYARIAH X - Toni Priyanto; Idqan Fahmi; Rifki Ismal (School of Business, Bogor Agricultural University (SB-IPB), 2016)
This study aims to determine the factors that affect the equity financing at the Islamic Banking which covers quantitative financing profit and loss sharing and to formulate policies to be performed by the management in maintaining the financing growth. The study was conducted by utilizing Autoregressive Distributed Lag (ARDL) model with variables including BI rate and inflation as the external factor. The test results of both external factors indicated a negative impact on both financing. BI rate as an indicator of the government's policy becomes the fastest variable affecting the equity financing i.e. at lag 1. Inflation comes as the macroeconomic indicator at lags 2, 9 and 10. All internal factors have a negative impact on both financing types except for the cost of education and training, and autoregressive variables. The fund of the third party influences the sharing of profit and loss (mudharabah) at lag 1 and at 9, meanwhile the capital adequacy ratio affects the profit sharing (mudharabah) at lag 8, and it affects the loss sharing (musyarakah) at lag 6. The cost of education and training has an effect on loss sharing at lag 5, and Islamic banking basic education affects profit financing at lag 2 whereas the trend of financing profit sharing is at lag 8 and loss sharing at lags 1 and 2 and since it autoregressive, it affects each financing of the current period.Keywords: autoregressive, dynamic, mudaraba, musharaka, profit and loss sharing financingABSTRAKPenelitian ini bertujuan mengetahui faktor-faktor yang memengaruhi pembiayaan berbasis bagi hasil pada Bank Syariah yang meliputi pembiayaan mudharabah dan musyarakah secara kuantitatif dan merumuskan kebijakan-kebijakan yang dapat dilakukan manajemen dalam menjaga pertumbuhan pembiayaannya. Penelitian dilakukan menggunakan Autoregressive Distributed Lag (ARDL) Model dengan variabel yang digunakan meliputi BI Rate dan inflasi sebagai faktor eksternal. Hasil pengujian kedua faktor eksternal memberikan pengaruh negatif terhadap kedua pembiayaan tersebut. BI Rate sebagai indikator kebijakan pemerintah menjadi variabel yang paling cepat memengaruhi pembiayaan berbasis bagi hasil yaitu pada lag 1. Berikutnya diikuti oleh inflasi sebagai indikator makroekonomi pada lag 2, 9 dan 10. Seluruh faktor internal memberikan pengaruh negatif terhadap kedua jenis pembiayaan kecuali biaya pendidikan dan pelatihan dan variabel autoregressive. Dana pihak ketiga memengaruhi pembiayaan mudharabah pada lag 1 dan 9. Sementara rasio kecukupan modal pada lag 8 memengaruhi pembiayaan mudharabah dan pada lag 6 memengaruhi pembiayaan musyarakah. Biaya pendidikan dan pelatihan memengaruhi pembiayaan musyarakah pada lag 5, pendidikan dasar perbankan syariah memengaruhi pembiayaan mudharabah pada lag 2. Sementara tren pembiayaan mudharabah pada lag 8 dan pembiayaan musyarakah pada lag 1 dan 2 sebagai autoregressive memengaruhi masing-masing pembiayaan pada periode kini.Kata kunci: autoregressive, dynamic, mudaraba, musharaka, profit and loss sharing financing